2020
DOI: 10.1108/jerer-07-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Dutch housing cycle and near-term market prospects

Abstract: Purpose This study is a practice undertaking examining three main concerns that currently dominate Dutch housing market debate: how long is the cycle, will the current house price inflation continue and is housing market in a bubble. With national house prices reaching record highs across all major cities, future market prospects became a topic of significant debate among policymakers, investors and the populace. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Despite, there are mixed findings on real estate pricing in general; some studies reveal that pricing behaviour is asymmetric (Annamalai et al , 2014; Cheng et al , 2019; Filotto et al , 2018), some studies found symmetric pricing behaviour of Covid-19 pandemic shock is also assumed to be an obstruction to the global economy which may be driven the negative expectation of investors’ income on HPI and could be further explained by rockets and feathers effects in support of the uneven movement of pricing behaviour. Obviously, series of studies investigated HPI from different perspectives due to undisputable contributions of real estate sector to the growth and development of national economy in particular and global economy in general (Annamalai et al , 2014; Apergis, 2015; Barros et al , 2012; Jadevicius and Gool, 2020; Mosquera et al , 2020; Tanrivermiş, 2020) and changes in the housing market could be dramatically observed (Kaya et al , 2019). Furthermore, findings on housing pricing behaviour remain inconclusive, therefore, related studies on asymmetric and symmetric of real estate pricing level discussed in the next two subsequent sections.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite, there are mixed findings on real estate pricing in general; some studies reveal that pricing behaviour is asymmetric (Annamalai et al , 2014; Cheng et al , 2019; Filotto et al , 2018), some studies found symmetric pricing behaviour of Covid-19 pandemic shock is also assumed to be an obstruction to the global economy which may be driven the negative expectation of investors’ income on HPI and could be further explained by rockets and feathers effects in support of the uneven movement of pricing behaviour. Obviously, series of studies investigated HPI from different perspectives due to undisputable contributions of real estate sector to the growth and development of national economy in particular and global economy in general (Annamalai et al , 2014; Apergis, 2015; Barros et al , 2012; Jadevicius and Gool, 2020; Mosquera et al , 2020; Tanrivermiş, 2020) and changes in the housing market could be dramatically observed (Kaya et al , 2019). Furthermore, findings on housing pricing behaviour remain inconclusive, therefore, related studies on asymmetric and symmetric of real estate pricing level discussed in the next two subsequent sections.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Besides that, during the Covid-19 pandemic, Turkey housing demand increased by about 23.5% (624,769 house units sold) (Global Property Guide, 2020; www.aa.com.tr, 2020), this is an indication for better future demand in the housing market of Turkey. Jadevicius and Gool (2020) reported that as at the time of conducting their research during Covid-19 pandemic, Dutch house price remains resilient.…”
Section: Empirical Findingsmentioning
confidence: 99%
See 3 more Smart Citations